The effect of heavy resistance exercise on the circadian rhythm of salivary Cortisol in women - Linder, E. E. (UW-L Journal of Undergraduate Research, 2003)
The purpose of this study was to determine the effects of exercise on salivary cortisol levels and the circadian rhythms of resistance-trained individuals. The subjects included seven resistance-trained women with the following characteristics [mean (SD)]: age 20.3(0.5) years; height163.0(4.0) cm; weight 59.0(5.8) kg. The testing period included two test days per week, incorporating a total of two days of "rest" and two days of "exercise". Subjects were randomly selected to participate on the"rest" and "exercise" days. Subjects were given a mandatoryworkout regimen to follow on the "exercise" days. The workout regimen consisted of the following exercises: hang pulls, bench press, leg press, upright rows, leg curls, military press, lat pulls, knee extensions, arm curls, and sit-ups. Throughout the testing period, subjects wererequired to keep a daily food and exercise log. Saliva samples were collected every two hours fora maximum of 16 hours during each testing day. Results of the testing indicated that cortisollevels increased immediately following exercise (p<0.05), but didn`t change significantly throughout the course of the day. This implies that while exercise did exert an effect on salivary cortisol production, it did not exert a similar effect on the circadian rhythm.